Association of low serum cholesterol levels with increased risk of primary intracerebral hemorrhage - Champawong, Kriangsak; Jetjumnong, Chumpon (Biomedical Sciences and Clinical Medicine, 2018)
Objective Several of the risk factors that increase the risk of primary intracerebral hemorrhage (PICH) are well documented. However, the association between serum cholesterol levels and PICH is still controversial. The objective of this study was to evaluate the correlation between serum cholesterol levels and PICH in Thai people. Methods In this retrospective case-control study, the serum cholesterol levels in PICH patients were compared to an independent control group in a primary care practice hospital in patients having yearly health check ups during the study. Participants were matched for age, gender, and race. The lowest quartile of the pooled blood lipid distribution was designated as the low cholesterol threshold. Results From 2015 to 2016, 55 cases of PICH and 112 control cases were enrolled. The mean total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) level in the PICH group was significantly lower than the control group (TC 176 mg/dL vs 211 mg/dL, p<0.001; LDL-C 107.2 mg/dL vs 145 mg/dL, p<0.001, respectively). A low LDL-C also increases the odds of hemorrhage by 11.78-fold (3.78-36.67, p< 0.001) after adjustment for covariates. Conclusions Low serum TC and LDL-C levels are associated with an increased risk of PICH in Thai people.